Analisis Strategi Pemasaran Dalam Meningkatkan Volume Penjualan Kue Home Industri Bay Tat Ricka Di Kota Bengkulu - Sri Ekowati; Nova Herliani (UNIVED Press, 2023)
This study aims to determine the analysis marketing strategy applied in increasing the sales volume of Bay Tat Ricka's home industry cakes in Bengkulu City. This type of research is a field research with a qualitative descriptive approach. Research informants are owners, employees and consumers of Bay Tat Ricka. The results show that the position of Bay Tat Ricka is in quadrant 1 with the coordinates of internal factors +0.49, and external factors +0.18 This means that Bay Tat Ricka is in a very favorable situation. Bay Tat Ricka has opportunities and strengths so he can take advantage of existing opportunities. The strategy that must be applied in this condition is to support an aggressive growth policy (Growth oriented strategy). The aggressive strategy that must be applied by Bay Tat Ricka Bengkulu City is the SO strategy, this strategy is a strategy made by utilizing all strengths to seize the opportunities that exist. The SO strategy that can be carried out by Bay Tat Ricka in Bengkulu City is to promote on social media, maintain taste so that consumers continue to subscribe, maintain product quality and maintain packaging in boxes with halal labeling.